Features of pathogenesis and treatment of breast cancer in the works of modern oncologists - Tamm, Tamara; Oleinik, Grigory; Prokopyuk, Oleksandra; Sadchykova, Maryna; Vinnik, Yuriy (ScienceRise: Medical Science, 2020)
To increase the effectiveness of treatment for breast cancer, representatives of various oncological schools use various approaches and scientific results obtained using high technologies, as evidenced by the analysis of scientific publications of specialists. The aim of this literature review was to analyze the influence of some scientific achievements using high technologies on modern ideas of oncologists about the pathogenesis of breast cancer and new approaches to increasing the efficiency of its treatment. Material and research methods. Scientific articles in journals specializing in Oncology, materials of scientific conferences, Internet resources Research results and their discussion. Unsatisfactory results of the treatment of breast cancer, frequent relapses of this pathology, high mortality, on the one hand, and the results of scientific studies using high technologies, on the other hand, led oncologists to search for new approaches to solving the problem by improving surgical, medicinal and radiation treatments. Conclusions. The search for new approaches to solving the issue of increasing the effectiveness of breast cancer treatment is carried out in different directions: in the field of improving surgical treatment methods, drug methods, taking into account inhibitors of immune control points, new drugs for targeted therapy and the theory of cancer stem cells. The development of new approaches to the treatment of breast cancer has great prospects in addressing the issue of increasing the effectiveness of its treatment